Mobile phone surveys: the Slovenian case study - Vehovar, Vasja (Metodološki zvezki, 2004)
In 2004, the number of mobile phone subscriptions in Slovenia reached the total number of inhabitants. Consequently, the fixed telephone coverage has started to decline; almost 10% of households are now available only over the mobile phone. With this, Slovenia positions itself as a typical EU country and can serve as a case study for issues related to mobile phone interview surveys. The paper addresses the general context of mobile phone usage and the calculations of mobile phone coverage rates. It also discusses the non-coverage problems related to mobile and mobile-only households. It is shown, that even with a relatively small non-coverage the corresponding estimates can be considerably biased, as in the case of the unemployment rate in the Slovenian Labour Force Survey. There are severe methodological problems with mobile phone interview surveys. In particular, a pilot mobile phone survey confirmed the disadvantages of costs, frames and response rates, at least when compared to fixed telephone surveys. In addition, the response rates are dramatically lower for less intensive mobile phone users. The comparisons of respondents in mobile phone surveys with the corresponding sub-samples in Labour Force Surveys and in fixed telephone surveys revealed some specific discrepancies in the socio-demographic structure. Due to non-coverage, the respondents in the mobile phone survey tend to be younger, higher educated, from larger households and are represented by a larger share of males. The non-response mechanism can additionally reinforce these effects (e.g gender), however it can also cancel them (e.g. age, household size). Special complexity arises from the diverse effects of the non-response components (refusal vs. non-contact). According to their attitudes towards mobile phone use, mobile phone users compose three distinct segments (intensive pragmatic and emotional users, less intensive users) that may behave differentially also during the mobile phone survey process.
Keywords: Telefonska anketa; Telephone opinion poll; Cellular telephones; Mobilni telefoni; Case study; Študija primera; Slovenia; Slovenija; ankete; telefonske ankete; zbiranje podatkov